Implementation Science, Professional Development, and Autism Spectrum Disorders. (January 2013) - Odom, Samuel L.; Cox, Ann W.; Brock, Matthew E.; ,
The increased prevalence of autism spectrum disorders (ASD) has intensified the need for high-quality special education services designed for children and youth with ASD and their families. Implementation science provides guidance for moving innovation, such as utilizing evidence-based practices for students with ASD, into regular practice in schools. The National Professional Development Center on ASD (NPDC) incorporated the principles of implementation science, the scientific knowledge about evidence-based practices, and the measurement of program quality into an intervention approach for students with ASD. This article presents the NPDC model as an example of using implementation science to build systems of professional development that increase the quality of services and promote teachers' use of evidence-based practices.